1988
DOI: 10.1210/endo-123-5-2167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Hormones on Urea Biosynthesis and Related Processes in Rat Liver*

Abstract: The results of the few studies on the effect of the thyroid status on nitrogen metabolism have been inconclusive and/or contradictory. In an attempt to elucidate this important relationship, we have studied the effect of experimental hypo- and hyperthyroidism on urea biosynthesis and related processes. We have found that the capacity of the liver to synthesize urea was increased in hypothyroid rats, as were the activities of the urea cycle enzymes; there were also changes in the activities of some related enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
2
23
1
2
Order By: Relevance
“…In a study of rats with hyperthyroidism, enhanced activity of the purine nucleotide cycle of exercising muscle was demonstrated that resulted in high serum ammonia concentrations in the rats and humans. 18,19 Ammonia is released during deamination of amino acids and is removed in blood by conversion into urea, and the high cellular metabolic rate caused by hyperthyroidism may result in accelerated protein catabolism and deamination. In the rat study, ammonia production was greater than lactate production, suggesting that purine catabolism was more accelerated than glycolysis in exercised muscle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of rats with hyperthyroidism, enhanced activity of the purine nucleotide cycle of exercising muscle was demonstrated that resulted in high serum ammonia concentrations in the rats and humans. 18,19 Ammonia is released during deamination of amino acids and is removed in blood by conversion into urea, and the high cellular metabolic rate caused by hyperthyroidism may result in accelerated protein catabolism and deamination. In the rat study, ammonia production was greater than lactate production, suggesting that purine catabolism was more accelerated than glycolysis in exercised muscle.…”
mentioning
confidence: 99%
“…In the rat study, ammonia production was greater than lactate production, suggesting that purine catabolism was more accelerated than glycolysis in exercised muscle. 18 This took over 2 months to resolve in humans. 19 Although, cats with hyperthyroidism still had mild increases in ammonia levels 6 weeks after iodine therapy, it might be that this would resolve completely if plasma ammonia was measured at 3 or 6 months after therapy.…”
mentioning
confidence: 99%
“…Hypothyroidism aggravates the hyperammonemic state due to increased nitrogen load that decreases protein synthesis, increases protein catabolism and decreases intestinal motility promoting bacterial production of ammonia and augmenting its absorption 4) . Moreover, hypothyroidism induces enzyme activity in the urea cycle leading to increased production of urea/ammonia 14) . In addition, myopathy triggered by hypothyroidism may also increase ammonia production in the muscles 3) , although thyroid myopathy was not obvious in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Os métodos para indução do hipertireoidismo agudo e crônico foram propostos por diversos autores (29). Em nosso estudo, os ratos receberam doses elevadas de T4 (20µg/100g de peso corporal), durante 20 dias, tempo suficiente para induzir tireotoxicose crônica.…”
Section: Discussionunclassified
“…Apesar da diferença do peso dos animais dos dois grupos, entre o início e o fim do experimento, não ter significância estatística, houve uma tendência (p=0,10) à perda de peso corporal nos animais do grupo estudo. Tal fato não invalida a hipótese de tireotoxicose, pois apesar do excesso dos hormônios tireoidianos causar quase sempre uma diminuição ponderal, por promover um acentuado aumento do metabolismo geral e por estimular diretamente a lipólise (30), também leva a um aumento do apetite (29), promovendo ingestão calórica maior, o que pode explicar a manutenção ou o ganho de peso em alguns dos animais do grupo estudo, visto que todos tiveram livre acesso à ração própria para a espécie durante todo o experimento.…”
Section: Discussionunclassified